Preparation method of high-performance aluminum nitride-based ceramic composite material
Patent Information
- Application Number
- CN202610920625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-09-01
AI Technical Summary
但是由于AlN难烧结特性与本征绝缘性,限制了其在静电卡盘的应用,为了使AlN陶瓷能够更好的应用于J-R型静电卡盘,需要就能得到结构致密、热导率高且电阻率符合要求的AlN基复合陶瓷材料
Smart Images

Figure CN122667937A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum nitride-based ceramics technology, and particularly to a method for preparing high-performance aluminum nitride-based ceramic composite materials. Background Technology
[0002] Aluminum nitride (AlN) possesses high thermal conductivity, low dielectric constant, high resistivity, wide bandwidth (Eg = 6.2 eV, RT), strong mechanical properties, chemical inertness, and a coefficient of thermal expansion similar to silicon, making it an excellent heat dissipation and packaging material. The theoretical thermal conductivity of AlN single crystals can reach 320 W / m·K, several times that of the traditional electronic substrate material Al₂O₃ (32 W / m·K). Therefore, AlN has become an ideal material for the manufacture of next-generation large-scale integrated circuits and semiconductor components.
[0003] In the semiconductor manufacturing field, electrostatic chucks, as a key component, play a crucial role in the stability and efficiency of the entire production process through their design and material selection. Given that electrostatic chucks need to operate stably in plasma environments and high-temperature corrosive gases, their materials must possess resistance to thermal shock, plasma impact, and chemical corrosion. AlN ceramics are considered the preferred material for manufacturing electrostatic chucks due to their high thermal conductivity, excellent chemical stability, low dielectric loss and dielectric constant, and a coefficient of thermal expansion similar to silicon. These properties not only ensure the structural integrity and functional stability of the electrostatic chuck under extreme operating environments but also contribute to improving the overall performance and reliability of the semiconductor manufacturing process. JR-type electrostatic chucks, in particular, have broad application prospects in the production of high-end semiconductor components due to their good electrostatic adsorption force and short desorption time at low voltages. However, the difficult sintering characteristics and intrinsic insulation of AlN limit its application in electrostatic chucks. To better utilize AlN ceramics in JR-type electrostatic chucks, it is necessary to obtain AlN-based composite ceramic materials with a dense structure, high thermal conductivity, and suitable resistivity. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing high-performance aluminum nitride-based ceramic composite materials, so as to solve the problems raised in the background art and prepare AlN-based composite ceramic materials with resistivity satisfying JR-type electrostatic chucks.
[0005] To solve the above-mentioned technical problems, the technical solution of the present invention is as follows:
[0006] A method for preparing a high-performance aluminum nitride-based ceramic composite material, the method comprising:
[0007] Mixed ball milling: AlN powder and conductive sintering aid powder are mixed, solvent and dispersant are added, and the mixed powder is wet ball milled in a nylon ball tank using alumina balls to obtain a mixed slurry. The conductive sintering aid powder is any one of TiB2 powder, Eu2O3 powder, and MoO2 powder or a mixture of two or more of them.
[0008] Green body preparation: The ball-milled slurry was dried in an oven, sieved, and the mixed powder was shaped into a disc in a graphite mold by unidirectional pressure to obtain a high-performance aluminum nitride-based ceramic composite green body;
[0009] Sintering: The high-performance aluminum nitride-based ceramic composite green body is placed in a hot pressing sintering furnace and sintered in a nitrogen atmosphere to form an AlN-based composite ceramic material.
[0010] Preferably, the AlN powder has a particle size of 1-5 μm and a purity of ≥99.9%, and the conductive sintering aid powder has a particle size of 2-5 μm and a purity of ≥99.8%.
[0011] Preferably, the conductive sintering aid powder is Eu2O3 powder, and the mass percentage of the Eu2O3 powder is 0.5 to 1.5 wt.%.
[0012] Preferably, the amount of solvent added is 30-50% of the total mass of AlN powder and conductive sintering aid powder, and the amount of dispersant added is 2-8% of the total mass of AlN powder and conductive sintering aid powder.
[0013] Preferably, the wet ball milling mixing speed is 100-400 r / min, and the wet ball milling mixing time is 5-10 h.
[0014] Preferably, the temperature of the ball-milled slurry in the oven is 90-120°C, the drying time is 20-30 hours, and the mesh size of the sieve after drying is 50-200 mesh.
[0015] Preferably, the sintering temperature of the high-performance aluminum nitride-based ceramic composite green body in the hot pressing sintering furnace is 1600-1950℃, the sintering time is 2-5 hours, and the sintering pressure is 15-25MPa.
[0016] Preferably, the resistivity of the AlN-based composite ceramic material is 10⁻⁶. 8 ~10 12 Ω·cm.
[0017] The above technical solution has the following beneficial effects:
[0018] This application employs a method of combining conductive sintering aid powder with aluminum nitride to prepare a high-performance, high-density aluminum nitride-based ceramic composite material. This aluminum nitride-based ceramic composite material not only retains the inherent high thermal conductivity of aluminum nitride ceramics, but also achieves a lower bulk resistivity and reduces the sintering temperature, thereby fully meeting the practical application requirements of the dielectric layer of JR-type electrostatic chucks. Attached Figure Description
[0019] Figure 1 The resistivity of AlN-based ceramic composites with different Eu2O3 doping contents is given.
[0020] Figure 2 The thermal conductivity of AlN-based ceramic composites with different Eu2O3 doping contents is given. Detailed Implementation
[0021] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0022] A method for preparing a high-performance aluminum nitride-based ceramic composite material, the method comprising:
[0023] Mixed ball milling: AlN powder and conductive sintering aid powder are mixed, solvent and dispersant are added, and the mixed powder is wet ball milled in a nylon ball tank using alumina balls to obtain a mixed slurry. The conductive sintering aid powder is any one of TiB2 powder, Eu2O3 powder, and MoO2 powder or a mixture of two or more of them.
[0024] Green body preparation: The ball-milled slurry was dried in an oven, sieved, and the mixed powder was shaped into a disc in a graphite mold by unidirectional pressure to obtain a high-performance aluminum nitride-based ceramic composite green body;
[0025] Sintering: The high-performance aluminum nitride-based ceramic composite green body is placed in a hot press sintering furnace and sintered in a nitrogen atmosphere to form an AlN-based composite ceramic material;
[0026] Specifically, the conductive sintering aid powder is any one of TiB2 powder, Eu2O3 powder, and MoO2 powder, or a mixture of two or more of them. Specifically, it can be any one of TiB2 powder, Eu2O3 powder, and MoO2 powder, or a mixture of any two, three, or four. The conductive sintering aid powder selected in this invention has a very low resistivity and does not affect the original thermal conductivity of aluminum nitride ceramics. Preparing it with AlN powder using wet ball milling can improve the bonding stability between AlN powder and conductive sintering aid, and is also beneficial to the subsequent sintering process, making the structure of AlN-based ceramic composite material more compact and the electrical properties more stable.
[0027] In some embodiments, the AlN powder has a particle size of 1–5 μm and a purity of ≥99.9%, and the conductive sintering aid powder has a particle size of 2–5 μm and a purity of ≥99.8%. Specifically, the AlN powder has a particle size of 1 μm or 5 μm and a purity of ≥99.9%, which can be 99.9%; the conductive sintering aid powder has a particle size of 2 μm or 5 μm and a purity of ≥99.8%, which can be 99.8%. If it is a mixed powder, the purity of each powder is... The particle size of AlN powder and conductive sintering aid powder is set based on the mass ratio of the two, with a purity of ≥99.8%. This not only ensures that the small-particle-size conductive sintering aid powder can be well and uniformly dispersed between AlN grains, but also ensures that the bonding between powders is improved during sintering, resulting in a high-performance aluminum nitride-based ceramic composite material with more uniform particle size. If the particle size of the conductive sintering aid powder is too large, it will be difficult to reduce the sintering temperature and it will be impossible to sinter a dense, low-volume resistivity dielectric layer suitable for JR-type electrostatic chucks.
[0028] In some embodiments, the conductive sintering aid powder is Eu2O3 powder, and the mass percentage of Eu2O3 powder is 0.5 to 1.5 wt.%; specifically, the mass percentage of Eu2O3 powder is 0.5 wt.% or 1.5 wt.%, and the corresponding mass percentage of AlN powder is 99.5 wt.% or 98.5 wt.%, or it can be 1.0 wt.%, and the corresponding mass percentage of AlN powder is 99 wt.%. The mass ratio of AlN powder to conductive sintering aid powder is to meet the low volume resistivity requirement of the JR type electrostatic chuck while maintaining good thermal conductivity.
[0029] In some embodiments, the amount of solvent added is 30-50% of the total mass of AlN powder and conductive sintering aid powder, and the amount of dispersant added is 2-8% of the total mass of AlN powder and conductive sintering aid powder; specifically, the amount of solvent added is 30% or 50% of the total mass of AlN powder and conductive sintering aid powder, and the solvent can be water or isopropanol, and the amount of dispersant added is 2% or 8% of the total mass of AlN powder and conductive sintering aid powder, and the dispersant can be BYK-111 dispersant.
[0030] In some embodiments, the wet ball milling speed is 100-400 r / min, and the wet ball milling time is 5-10 h; specifically, the wet ball milling speed is 100 r / min or 400 r / min, or even 200 r / min or 300 r / min, and the wet ball milling time is 5 h or 10 h.
[0031] In some embodiments, the ball-milled slurry is dried in an oven at a temperature of 90–120°C for 20–30 hours, and the sieve mesh size after drying is 50–200 mesh. Specifically, the ball-milled slurry is dried in an oven at a temperature of 90°C or 120°C for 20 or 30 hours, and the sieve mesh size after drying is 50 or 200 mesh, or even 100 or 150 mesh.
[0032] In some embodiments, the sintering temperature of the high-performance aluminum nitride-based ceramic composite green body in the hot pressing sintering furnace is 1600–1950°C, the sintering time is 2–5 hours, and the sintering pressure is 15–25 MPa; specifically, the sintering temperature of the high-performance aluminum nitride-based ceramic composite green body in the hot pressing sintering furnace is 1600°C or 1950°C, or even 1800°C, the sintering time is 2 hours or 5 hours, and the sintering pressure is 15 MPa or 25 MPa.
[0033] In some embodiments, the resistivity of the AlN-based composite ceramic material is 10. 8 ~10 12 Ω·cm, resistivity in 10 8 ~10 12 Within the Ω·cm range, the prepared AlN-based composite ceramic material can meet the usage requirements of JR-type electrostatic chucks.
[0034] This application employs a method of combining conductive sintering aid powder with aluminum nitride to prepare a high-performance, high-density aluminum nitride-based ceramic composite material. This aluminum nitride-based ceramic composite material not only retains the inherent high thermal conductivity of aluminum nitride ceramics, but also achieves a lower bulk resistivity and reduces the sintering temperature, thereby fully meeting the practical application requirements of the dielectric layer of JR-type electrostatic chucks.
[0035] Example 1
[0036] A method for preparing a high-performance aluminum nitride-based ceramic composite material, specifically comprising:
[0037] Weigh 99.5 wt.% AlN powder (powder purity ≥ 99.9%, powder particle size 1-5 μm) and 0.5 wt.% Eu2O3 powder (powder purity ≥ 99.8%, powder particle size 2-5 μm) and mix them to obtain a mixed powder. Add the mixed powder to a ball mill mixer, and add 40% isopropanol and 3% BYK-111 dispersant to the ball mill jar. Use an alumina ball mill for wet ball milling to mix evenly, wherein the ball milling speed is 350 r / min and the ball milling time is 8 h.
[0038] The mixed slurry was then dried in an oven at 110°C for 26 hours, and the dried mixed powder was then passed through an 80-mesh sieve. Next, the mixed powder was pressed into cylinders with a diameter of 30 mm and a thickness of 10 mm using unidirectional pressure.
[0039] Finally, the sample was placed in a hot pressing furnace at 1800 ℃ and sintered for 3 hours to obtain a high-performance aluminum nitride-based ceramic composite material.
[0040] Example 2
[0041] A method for preparing a high-performance aluminum nitride-based ceramic composite material, specifically comprising:
[0042] Weigh 99 wt.% AlN powder (powder purity ≥ 99.9%, particle size 1–5 μm) and 1 wt.% Eu2O3 powder (powder purity ≥ 99.8%, particle size 2–5 μm) and mix them to obtain a mixed powder. Add the mixed powder to a ball mill mixer, and add 40% isopropanol and 3% BYK-111 dispersant to the ball mill jar. Use an alumina ball mill for wet ball milling to mix evenly, wherein the ball milling speed is 350 r / min and the ball milling time is 8 h.
[0043] The mixed slurry was then dried in an oven at 110°C for 26 hours, and the dried mixed powder was then passed through an 80-mesh sieve. Next, the mixed powder was pressed into cylinders with a diameter of 30 mm and a thickness of 10 mm using unidirectional pressure.
[0044] Finally, the sample was placed in a hot pressing furnace at 1800 ℃ and sintered for 3 hours to obtain a high-performance aluminum nitride-based ceramic composite material.
[0045] Example 3
[0046] A method for preparing a high-performance aluminum nitride-based ceramic composite material, specifically comprising:
[0047] Weigh 98.5 wt.% AlN powder (powder purity ≥99.9%, powder particle size 1–5 μm) and 1.5 wt.% Eu2O3 powder (powder purity ≥99.8%, powder particle size 2–5 μm) and mix them to obtain a mixed powder. Add the mixed powder to a ball mill mixer, and add 40% isopropanol and 3% BYK-111 dispersant to the ball mill jar. Use an alumina ball mill for wet ball milling to mix evenly, wherein the ball milling speed is 350 r / min and the ball milling time is 8 h.
[0048] The mixed slurry was then dried in an oven at 110°C for 26 hours, and the dried mixed powder was then passed through an 80-mesh sieve. Next, the mixed powder was pressed into cylinders with a diameter of 30 mm and a thickness of 10 mm using unidirectional pressure.
[0049] Finally, the sample was placed in a hot pressing furnace at 1800 ℃ and sintered for 3 hours to obtain a high-performance aluminum nitride-based ceramic composite material.
[0050] Comparative Example 1
[0051] A method for preparing aluminum nitride ceramics, differing from Examples 1, 2, and 3 in that Eu2O3 powder is not added, specifically including:
[0052] Weigh out pure AlN powder (powder purity ≥ 99.9%, powder particle size 1-5 μm), add it to a ball mill mixer, and add 40% isopropanol and 5% BYK-111 dispersant to the ball mill jar. Use aluminum nitride ball mills for wet ball milling to mix evenly, with a ball milling speed of 350 r / min and a ball milling time of 8 h.
[0053] The mixed slurry was then dried in an oven at 110°C for 26 hours, and the dried mixed powder was then passed through an 80-mesh sieve. Next, the mixed powder was pressed into cylinders with a diameter of 30 mm and a thickness of 10 mm using unidirectional pressure.
[0054] Finally, the sample was placed in a hot press sintering furnace at 1800℃ and sintered for 3 hours to obtain aluminum nitride ceramic material.
[0055] Depend on Figure 1It is evident that the high-performance aluminum nitride-based ceramic composite material of this invention significantly reduces the bulk resistivity, meeting the requirements of the JR-type electrostatic chuck dielectric adsorption layer for freely moving electrons. Examples 1 and Comparative Example 1 show that, compared to pure AlN ceramic, the aluminum nitride-based ceramic composite material with an Eu₂O₃ doping content of 0.5 wt% exhibits lower resistivity because the formed aluminate liquid phase promotes the sintering process, resulting in well-developed, dense hexagonal grains of AlN with a larger grain size. Examples 1 and 2 show that when the Eu₂O₃ doping content increases to 1.0 wt%, the formed EuAlO₃ is continuously distributed at the AlN grain boundaries, forming a continuous conductive network structure. Current bypasses the high-resistivity AlN grains and conducts through the low-resistivity EuAlO₃, significantly reducing the resistivity of the aluminum nitride-based ceramic composite material. Examples 2 and 3 show that with further increases in the Eu₂O₃ doping content, the content of the Eu₄Al₂O₉ phase in the AlN ceramic continuously increases, resulting in a more significant effect on purifying the AlN lattice and reducing the concentration of conductive defects. Meanwhile, the high-viscosity liquid phase accumulates at the triple grain boundaries, hindering grain growth and homogenization. These factors combined cause the resistivity of the aluminum nitride-based ceramic composite material to continuously increase.
[0056] Depend on Figure 2 It is evident that the high-performance aluminum nitride-based ceramic composite material in this invention also significantly enhances thermal conductivity, meeting the requirement for good heat dissipation in JR-type electrostatic chucks during semiconductor manufacturing. Examples 1 and 2 and Comparative Example 1 show that the aluminum nitride-based ceramic composite material exhibits higher thermal conductivity than pure AlN, indicating the purifying effect of Eu2O3 on AlN grains and reducing the oxygen concentration in the AlN lattice. Grain size affects the thermal conductivity of the material because the presence of grain boundaries hinders heat conduction. Grain boundaries are generally the accumulation sites of various defects, such as dislocations and inclusions, which negatively impact heat conduction. Larger grain sizes mean a reduction in the number of grain boundaries, thus achieving higher thermal conductivity. Examples 2 and 3 show that as the Eu2O3 content continues to increase, the Eu4Al2O9 phase increases, reducing the contact area between AlN grains, increasing grain boundary thermal resistance, and resulting in a slight decrease in the thermal conductivity of the high-performance aluminum nitride-based ceramic composite material.
[0057] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance aluminum nitride-based ceramic composite material, characterized in that, The preparation method includes: Mixed ball milling: AlN powder and conductive sintering aid powder are mixed, solvent and dispersant are added, and the mixed powder is wet ball milled in a nylon ball tank using alumina balls to obtain a mixed slurry. The conductive sintering aid powder is any one of TiB2 powder, Eu2O3 powder, and MoO2 powder or a mixture of two or more of them. Green body preparation: The ball-milled slurry was dried in an oven, sieved, and the mixed powder was shaped into a disc in a graphite mold by unidirectional pressure to obtain a high-performance aluminum nitride-based ceramic composite green body; Sintering: The high-performance aluminum nitride-based ceramic composite green body is placed in a hot pressing sintering furnace and sintered in a nitrogen atmosphere to form an AlN-based composite ceramic material.
2. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The AlN powder has a particle size of 1–5 μm and a purity of ≥99.9%, while the conductive sintering aid powder has a particle size of 2–5 μm and a purity of ≥99.8%.
3. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The conductive sintering aid powder is Eu2O3 powder, and the mass percentage of the Eu2O3 powder is 0.5 to 1.5 wt.%.
4. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The amount of solvent added is 30-50% of the total mass of AlN powder and conductive sintering aid powder, and the amount of dispersant added is 2-8% of the total mass of AlN powder and conductive sintering aid powder.
5. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The wet ball milling speed is 100-400 r / min, and the wet ball milling time is 5-10 h.
6. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The ball-milled slurry is dried in an oven at a temperature of 90–120°C for 20–30 hours, and then sieved to a mesh size of 50–200.
7. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The high-performance aluminum nitride-based ceramic composite green body is sintered at a temperature of 1600–1950°C in a hot pressing sintering furnace for 2–5 hours and at a pressure of 15–25 MPa.
8. The method for preparing a high-performance aluminum nitride-based ceramic composite material according to claim 1, characterized in that, The resistivity of the AlN-based composite ceramic material is 10. 8 ~10 12 Ω·cm.